Vliv příčného ztužení oblouků dvoukolejného železničního mostu při dynamické odezvě - Bureš, Vojtěch (Vysoké učení technické v Brně. Fakulta stavební, 2024)
Předmětem této diplomové práce je statická a dynamická analýza oblouků ocelového železničního mostu a zkoumaní vlivu jejich ztužení. Byl vytvořen deskostěnový model v programu Ansys, ten následně zatížen a staticky posouzen dle teorie druhého řádu s vloženými imperfekcemi. Dynamická analýza se věnovala vlivu ztužení na dlouhodobou životnost konstrukce. Výsledky na modelech s obloukovými ztužidly a bez ztužidel byly porovnány.

The subject of this diploma thesis is static and dynamic analysis of arches of a steel railway bridge and investigation of the influence of their stiffening. A shell model was created in Ansys, which was then loaded and statically checked according to the second-order analysis with inserted imperfections. The dynamic analysis focused on the influence of stiffening on the long-term service life of the structure. The results on models with and without arched stiffener were compared.
The influence of the transverse stiffening of the arches of a double-track railway bridge in the dynamic response
Keywords: Ansys; nelineární analýza; imperfekce oblouku; modální analýza; dynamický součinitel; dynamická analýza; oblouková ztužidla; Ansys; nonlinear analysis; arch imperfection; modal analysis; dynamic coefficient; dynamic analysis; arch stiffeners